Empowering the Kuansing care community to optimize the functions of the eco-education park in the Pulau Bungin Urban Forest - Syafrinal Syafrinal; Evi Suryawati; Agus Mandar; Putri Rahma Dianti (Universitas Muhammadiyah Malang, 2025)
The Pulau Bungin Urban Forest, covering an area of 4.94 hectares, is a green open space in Teluk Kuantan City that functions as the city's lungs and a biodiversity conservation area. This urban forest serves as an eco-education park and is the commencement site for the annual national Pacu Jalur. The administration of the urban forest is overseen by the Environmental Agency and its partner, the Kuansing Care Community (KPK), as the driving force behind environmental management. This community service initiative seeks to empower the KPK to coordinate and enhance the efficacy of environmental management within the urban forest of the island. The community service occurred from July 8 to August 30, 2025, employing training and mentoring methods. The primary activities include organizational SOP training, TOSS training, and ecobrick training. The evaluation of the KPK's organizational capabilities post-training was classified as good, with a score range of 80.7 to 83. This condition indicates that the KPK's organizational management capabilities are progressing effectively. Empowerment for tangible environmental management actions through TOSS and ecobrick training showed an increase in participant competency of 21%, with an average ranging from 83.3 to 89.4 (good category). Overall, the activities showed positive changes in the competency and skills of KPK partners. This activity is expected to improve the quality of the KPK's organization and concrete actions in managing a sustainable environment, thereby directly contributing to the attainment of SDGs points 11, 15, and 17.